Diagnostic ultrasound imaging : inside out - Szabo, Thomas L. (Academic Press series in biomedical engineering., 2004)
Diagnostic Ultrasound Imaging provides a comprehensive introduction to and a state-of-the-art review of the essential science and signal processing principles of diagnostic ultrasound. The progressive organization of the material serves beginners in medical ultrasound science and graduate students as well as design engineers, medical physicists, researchers, clinical collaborators, and the curious. This it the most comprehensive and extensive work available on the core science and workings of advanced digital imaging systems, exploring the subject in a unified, consistent and interrelated manner. From its antecedents to the modern day use and prospects for the future, this it the most up-to-date text on the subject. Diagnostic Ultrasound Imaging provides in-depth overviews on the following major aspects of diagnostic ultrasound: absorption in tissues; acoustical and electrical measurements; beamforming, focusing, and imaging; bioeffects and ultrasound safety; digital imaging systems and terminology; Doppler and Doppler imaging; nonlinear propagation, beams and harmonic imaging; scattering and propagation through realistic tissues; and tissue characterization. Based on the author's over thirty-five years of experience in developing laboratory methodology and standards and conducting research in ultrasound. Conveys the fundamentals of diagnostic ultrasound as well as state-of-the-art reviews of major topics. from a historical perspective. Matlab MATLAB problems and examples included. . MATLAB problems and examples included.